2012
DOI: 10.1177/1741143212456913
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Implications of Faculty Performance Standards

Abstract: Expectations and how they are communicated influence employees' motivation, effort, goals, efficacy and performance. This study examined faculty performance evaluation standards and processes of 60 academic departments in research universities for motivationally relevant elements. Characteristics were systematically analysed to understand their content and motivational implications. They were examined for features influential on employee engagement, effort, persistence, innovation and organizational commitment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…36 Literature has shown that unclear promotion policies can lead to unrealistic expectations and perceived unfairness among employees, which can then result in negative work outcomes such as low job satisfaction, increased turnover, and poor organization commitment. 1,[37][38][39][40][41][42][43][44][45][46] Therefore, we believe that clear objective measures and transparency in PT guidance documents can improve faculty members' perceptions of procedural justice, thus resulting in more positive outcomes such as satisfaction with faculty position/career and high organizational commitment among faculty. 1, 37-39, 42, 45 This in turn builds clear expectations for faculty and may also prevent optimism bias toward the PT process.…”
Section: A J P Ementioning
confidence: 99%
See 3 more Smart Citations
“…36 Literature has shown that unclear promotion policies can lead to unrealistic expectations and perceived unfairness among employees, which can then result in negative work outcomes such as low job satisfaction, increased turnover, and poor organization commitment. 1,[37][38][39][40][41][42][43][44][45][46] Therefore, we believe that clear objective measures and transparency in PT guidance documents can improve faculty members' perceptions of procedural justice, thus resulting in more positive outcomes such as satisfaction with faculty position/career and high organizational commitment among faculty. 1, 37-39, 42, 45 This in turn builds clear expectations for faculty and may also prevent optimism bias toward the PT process.…”
Section: A J P Ementioning
confidence: 99%
“…Although a balance between explicitly defined criteria for PT and more flexible holistic guidelines that allow faculty more leeway in making their own individualized case for PT may seem ideal, Hardre and Kollman argue that many PT guidance documents are "largely amotivating" in part because of their lack of specific guidance. 1 Among their recommendations is clear, precise language that helps faculty align their individual performance plans with evaluative criteria, which helps to support faculty performance in a motivationally positive way. In simple terms, this allows faculty to know what to do to succeed in their career advancement while being able to set their own personally meaningful pathway to achieve these criteria.…”
Section: A J P Ementioning
confidence: 99%
See 2 more Smart Citations
“…Success in academic publishing reflects the quality and type of work valued by the scholarly community as a whole and by specific disciplines, including degree of consensus (Bedeian, ; Hargens, ). Maintaining evaluative quality standards is a high priority for any academic community (Erren, ; Macnab & Thomas, ) because evaluative criteria and specifications substantively influence the nature and outcomes of evaluative processes and decisions (Hardré, Cox, & Kollmann, ; Hardré & Kollmann, ). Peer review by volunteer expert scholars is at the heart of the journal publishing process, and it has been estimated that each review requires 1 to 6 hours (Hojat, Gonnella, & Calleigh, ).…”
Section: Introductionmentioning
confidence: 99%